PENERAPAN ALGORITMA K-MEANS DAN ALGORITMA NAÏVE BAYES DALAM PEMILIHAN KONSENTRASI JURUSAN SISWA DI SMA ISLAM TA’ALUMUL HUDA BUMIAYU - Rito Cipta Sigitta; M Ghozi Ghozali; Nurul Mega Saraswati (Informatika Publisher, 2021)
The determination of majors in high school, vocational high school and Madrasah Aliyah is done at the beginning of school. Sma Islam Ta'alumul Huda Bumiayu implemented the 2013 education unit level curriculum as a foundation in the cornering process. The selection of the concentration of majors should take into account the interests and academic ability of students so as not to have difficulty in absorbing and understanding the material, to overcome the above problems is required methods that can provide reference for students in selecting the concentration of majors. The methods used are the K-Means clustering algorithm and the Naïve Bayes algorithm. Classification results using the K-Means clustering algorithm and Naive Bayes obtained 80% accuracy.